Nanocomposite of Ag-Doped ZnO and AgO Nanocrystals as a Preventive Measure to Control Biofilm Formation in Eggshell and Salmonella spp. Entry Into Eggs - Fonseca, Belchiolina Beatriz; Silva, Paula Luiza Alves Pereira Andrada; Silva, Anielle Christine Almeida; Dantas, Noelio Oliveira; de Paula, Aline Teodoro; Olivieri, Otavio Cintra Lemos; Beletti, Marcelo Emilio; Rossi, Daise Aparecida; Goulart, Luiz Ricardo (Frontiers in Microbiology, 2019)
Salmonella spp. is an important foodborne agent of salmonellosis, whose sources in humans often include products of avian origin. The control of this bacterium is difficult especially when Salmonella spp is organized into biofilms. We hypothesized that the novel nanocomposites of ZnO nanocrystals doped with silver (Ag) and silver oxide (Ag2O) nanocrystals (ZnO:Ag-AgO) synthesized by the coprecipitation method could control or prevent the formation of Salmonella Enteritidis (SE) and Salmonella Heidelberg (SH) biofilm and its entry into turkey eggs. The diffraction characteristics of ZnO and Ag2O showed sizes of 28 nm and 30nm, respectively. The Zn to Ag substitution into the ZnO crystalline structure was evidenced by the ionic radius of Ag+2 (1.26 Å), which is greater than Zn+2 (0.74 Å). For the SE analyses post-biofilm formation, the ZnO:Ag-AgO was not able to eliminate the biofilm, but the bacterial load was lower than that of the control group. Additionally, SE was able to infiltrate into the eggs and was found in both albumen and yolk. For the SH analyses applied onto the eggshells before biofilm formation, the ZnO:Ag-AgO treatment prevented biofilm formation, and although the bacterium infiltration into the eggs was observed in all treated groups, it was significantly smaller in ZnO:Ag-AgO pre-treated eggs, and SH could not reach the yolk. There was no difference in pore size between groups; therefore, the inhibition of biofilm formation and the prevention of bacterium entry into the egg were attributable to the use of ZnO:Ag-AgO, which was not influenced by the egg structure. Although the amount of Ag and Zn in the shell of the ZnO:Ag-AgO group was greater in relation to the control, this difference was not detected in the other egg components. In the search for new measures that are effective, safe and viable for controlling microorganisms in poultry farming, the application of a nanocomposite of Ag-doped ZnO and Ag2O nanocrystals appears as an alternative of great potential to prevent Salmonella sp biofilms in eggshells and other surfaces.